Peta Koalisi Partai-Partai Politik di Indonesia pada Pemilihan Presiden dan Wakil Presiden Pasca Orde Baru (Universitas Medan Area, 2019)
Reformation became an important moment of democratization in Indonesia. The two important political changes that occur in reformation era are the freedom to establish political parties and the electoral system. Such changes have an impact on the emergence of a coalition phenomenon in Indonesia, because general elections with multiparty systems are unable to produce a majority vote in parliament. This paper aims to map and analyze the dinamic of the political party coalition in Indonesia’ presidential election in the reform era within coalition theories by Riker, Katz&Mair and Swaan. Using a qualitative approach and secondary data from media and literature, the main factor that influence the formation of coalitions in the presidential elections in the reform era is political pragmatism. It Political pragmatism makes political partiesparty politics as a cartel party that becomes the agent of the state and employ the resources of the state to ensure their party’ survival. Pragmatism ultimately makes the ideology is not a binding factor in building a coalition, but simply to maximize power.